2001
DOI: 10.1093/aje/153.5.490
|View full text |Cite
|
Sign up to set email alerts
|

Serum Triglycerides and Risk of Coronary Heart Disease among Japanese Men and Women

Abstract: To examine the relation of triglycerides with coronary heart disease among populations with low mean total cholesterol, the authors conducted a 15.5-year prospective study ending in 1997 of 11,068 Japanese aged 40-69 years (4,452 men and 6,616 women with mean total cholesterol = 4.73 mmol/liter and 5.03 mmol/liter, respectively), initially free of coronary heart disease or stroke. There were 236 coronary heart disease events comprising 133 myocardial infarctions, 68 angina pectoris events, and 44 sudden cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
242
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 296 publications
(266 citation statements)
references
References 41 publications
11
242
0
1
Order By: Relevance
“…Although the justification for the use of the same cutoff point as fasting status is debated, the data represented by nonfasting triglycerides can be used because of its significant predictive ability with regard to ischemic heart disease. 35 In conclusion, this study provides epidemiological evidence that the metabolic syndrome was associated with the risks of ischemic heart disease and ischemic stroke, but not with the risk of hemorrhagic stroke. The metabolic syndrome based on the AHA/NHLBI criteria predicts the risk of ischemic cardiovascular disease better than that based on the IDF criteria among less-obese populations.…”
Section: Discussionmentioning
confidence: 63%
“…Although the justification for the use of the same cutoff point as fasting status is debated, the data represented by nonfasting triglycerides can be used because of its significant predictive ability with regard to ischemic heart disease. 35 In conclusion, this study provides epidemiological evidence that the metabolic syndrome was associated with the risks of ischemic heart disease and ischemic stroke, but not with the risk of hemorrhagic stroke. The metabolic syndrome based on the AHA/NHLBI criteria predicts the risk of ischemic cardiovascular disease better than that based on the IDF criteria among less-obese populations.…”
Section: Discussionmentioning
confidence: 63%
“…Even though TG is a well known risk factor for atherosclerosis (20), a few previous studies reported the relation between nonfasting TG and CAD in Japanese population (10) …”
Section: F I D E N C E I N T E R V a L S F O R F A S T I N G P L A S mentioning
confidence: 99%
“…Studies conducted in Taiwan have also suggested that triglyceride is associated with hypertension in patients with T2DM and may also be associated with the progression of albuminuria [13,14]. Indeed, in the Asian population, hypertriglyceridemia may be more important than LDL-C as a risk factor for CVD in diabetic patients and non-diabetic patients [15][16][17]. In this article, we review the role of TG in CVD in patients with T2DM in Asian populations.…”
Section: Introductionmentioning
confidence: 99%